Rana ulukalensis Nakatani, 1969, A Junior Synonym of Rana tweediei Smith, 1935 (Amphibia: Anura: Dicroglossidae) - Das, Indraneil (The Herpetological Society of Japan, 2010)
The nomen Rana ulukalensis, occupied by Nakatani (1969) for a frog collected from the foot of “Mount Ulu Kali”, situated at the headwaters of Batang Kali, a river NNE of Kuala Lumpur, Malaysia, is shown to be a subjective junior synonym of Rana tweediei Smith, 1935, whose currently valid name is Limnonectes tweediei (Smith, 1935).